Impact of the information and communication sector on spatial development and post-war recovery of creative industries in Ukraine's economy - Marianna Kichurchak (Економічний форум)
The processes of digitalization concerning households, firms and state institutions facilitate to the rapid development of the information and communication sector (ICS) enhancing the position of creative industries at the regional level and fostering structural changes in the national economy. The purpose of the article is to explore chief trends in the economic and social development of the ICS by region in order to determine its role in the post-war recovery of creative industries in Ukraine’s economy. The following scientific methods were used: induction and deduction, comparative and spatial analysis, multiple regression analysis. The author has revealed that, in 2014–2020, given indicators of value added at factor costs of business entities, the number of active business entities in this sector, the number of persons employed by business entities and turnover, the positions of the ICS have strengthened in the regions of Ukraine, which favourably affected the development of creative industries. It is determined that there is a spatial differentiation in the social and economic development of the ICS, the basis of which is the peculiarities in formation of human potential and sectoral specialization by region. It is specified that the war in Ukraine has negatively affected the growth in the ICS as components of creative industries due to logistics complications, electricity shortages, intensity of hostilities and missile strikes. Based on the methodology of multiple regression analysis, the following factors concerning the development of the ICS at the regional level are defined: the volume of investment by GRP, conditions for export of services in this sector and the demographic situation. It is highlighted that the ICS is able to adapt to activities under martial law, increasing its influence on the development of creative industries in Ukraine and forming favourable social and economic prerequisites to resume economic growth in these industries after the end of the war. The research findings will be beneficial to substantiate the feasibility of using a number of measures to stimulate the development of the ICS so as to intensify its participation in the post-war reconstruction of creative industries by regions of Ukraine concerning improvement of the demographic situation through the formation of favourable social conditions for the return of the population, enhancement of the investment climate and promotion of export of services